2020
DOI: 10.7441/joc.2020.02.05
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus of Competition Freedom and the Efficiency of Microfinance Institutions

Abstract: The main purpose of this paper is to examine the effects of regulatory efficiency and market openness, two dimensions of competition freedom, on the efficiency of microfinance institutions (MFIs) in both its social and financial aspects. In addition, this study also examines the specific determinants of MFIs and macroeconomic conditions, two other potential variables that may influence MFIs efficiency. Within this study, two stages of analysis were conducted. In the first stage, the data envelopment analysis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 27 publications
(42 reference statements)
4
33
0
Order By: Relevance
“…In conclusion, the results in Panel I (all years) show that the MFIs from all countries over the years are more focused on financial efficiency to maximize the profit rather than reaching out the poorest of the poor citizens since the average and rank average of financial are higher than social efficiency under both parametric and non-parametric tests. This result is consistent with the studies that conducted by Hussain et al (2020), Zainal et al (2019Zainal et al ( , 2020, Widiarto and Emrouznejad (2015) and Lebovics et al (2016). This result shows that MFIs are more concern on pursuing financial stability to ensure they can meet the social needs by granting more loans to the poor consumers with the profit of MFIs to enhance the social efficiency.…”
Section: Social and Financial Efficiencies Of Mfissupporting
confidence: 91%
See 2 more Smart Citations
“…In conclusion, the results in Panel I (all years) show that the MFIs from all countries over the years are more focused on financial efficiency to maximize the profit rather than reaching out the poorest of the poor citizens since the average and rank average of financial are higher than social efficiency under both parametric and non-parametric tests. This result is consistent with the studies that conducted by Hussain et al (2020), Zainal et al (2019Zainal et al ( , 2020, Widiarto and Emrouznejad (2015) and Lebovics et al (2016). This result shows that MFIs are more concern on pursuing financial stability to ensure they can meet the social needs by granting more loans to the poor consumers with the profit of MFIs to enhance the social efficiency.…”
Section: Social and Financial Efficiencies Of Mfissupporting
confidence: 91%
“…Numerous of studies stated the MFIs role is focusing on the social performance by alleviating the poverty via assisting the poor people by providing them a platform for the financial service since they are not entitled or do not have access to deal with the financial institutions (Rauf & Mahmood, 2009). Hussain et al (2020) examine the MFIs social and financial efficiency with the impact of the competition freedom in Cambodia, Malaysia, Indonesia, Thailand and Philippines over the years from 2011 to 2017. The findings conclude that the overall social efficiency of MFIs is significantly less efficient than financial efficiency except for the MFIs in Thailand.…”
Section: Literature Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…ey considered the IOV for the transport context with four different dimensions, namely, general information of the vehicle, safety information of the vehicle, motion control of individuals, and motion control of a group [36]. Similarly, a study conducted by Händel, Ohlsson, Ohlsson, Skog, and Nygren [37] suggested to include the smart-phone technology to automate the vehicle for traffic monitoring as well as for insurance purpose usage to measure the Internet of the vehicle concept.…”
Section: Concern For the Internet Of Vehicle Information Privacy (Cfiovip)mentioning
confidence: 99%
“…Notably, the global strategy has several benefits, including the competitive advantages that positively affect business performance. As business performance has major importance in getting success in the market (Addison et al, 2020;Hafiz & Sary, 2020;Hussain et al, 2020), it is essential to promote global strategy.…”
Section: Introductionmentioning
confidence: 99%